Titanium nanoparticles doping of 5CB infiltrated microstructured optical fibers - Siarkowska, Agata; Chychłowski, Miłosz; Woliński, Tomasz Ryszard; Dybko, Artur (Photonics Letters of Poland, 2016)
Optical properties 5CB liquid crystal (LC) cells and 5CB infiltrated microstructured optical fibers doped with 1 wt.% titanium nanoparticles (NPs) of the size 100nm, have been studied. NPs were found to modify properties of both LC cells and LC-infiltrated fibers. Preliminary thermo-optic properties of photonic liquid crystal fiber with Ti-doped 5CB were researched. Additionally, preliminary electro-optic characteristic of the nanoparticles doped LC cell have been obtained. Full Text: PDF References C.V. Rajaram, S.D. Hudson, L.C. Chien, "Morphology of Polymer-Stabilized Liquid Crystals", Chem. Mater.7, 2300 (1995). CrossRef I. Dierking, G. Scalia, P. Morales, "Liquid crystal–carbon nanotube dispersions", J. Appl. Phys. 97, 044309 (2005). CrossRef J. Mirzaei, M. Urbanski, H.S. Kitzerow, T. Hegmann, "Hydrophobic gold nanoparticles via silane conjugation: chemically and thermally robust nanoparticles as dopants for nematic liquid crystals", Philos. Trans. A. Math. Phys. Eng. Sci. 371, 20120256 (2013). CrossRef W. Chen, P. Chen, C. Chao, "Effect of Insulating Nanoparticles Doping on Electro-Optical Characteristics in Nematic Liquid Crystal Cells", Mol. Cryst. Liquid Cryst. 507, 253 (2009). CrossRef N. Podoliak, O. Buchnev, M. Herrington, E. Mavrona, M. Kaczmarek, A. G. Kanaras, E. Stratakis, J. Blach, J. Henninot, M. Warenghem, "Elastic constants, viscosity and response time in nematic liquid crystals doped with ferroelectric nanoparticles", RSC Advances 4, 46068 (2014). CrossRef M. Mishra, R. Dabrowski, J.K. Vij, A. Mishra, R. Dhar, "Electrical and electro-optical parameters of 4?-octyl-4-cyanobiphenyl nematic liquid crystal dispersed with gold and silver nanoparticles", Liq. Cryst. 42, 1580 (2015). CrossRef J. Mirzaei, M. Urbanski, H.S. Kitzerow, T. Hegmann, "Hydrophobic gold nanoparticles via silane conjugation: chemically and thermally robust nanoparticles as dopants for nematic liquid crystals", Philos. Trans. A. Math. Phys. Eng. Sci. 371, 20120256 (2013). CrossRef K.K. Vardanyan, D.M. Sita, R.D. Walton, W.M. Saidel, K.M. Jones, "Cyanobiphenyl liquid crystal composites with gold nanoparticles", RSC Advances 3, 259 (2013). CrossRef E. Ouskova, D. Lysenko, S. Ksondzyk, L. Cseh, G. Mehl, V. Reshetnyak, Y. Reznikov, "Strong Cubic Optical Nonlinearity of Gold Nanoparticles Suspension in Nematic Liquid Crystal", Mol. Crystals Liquid Crystals 545, 1347 (2011). CrossRef T.R. Woliński, K. Szaniawska, K. Bondarczuk, P. Lesiak, A.W. Domański, R. Dąbrowski, E. Nowinowski- Kruszelnicki, J. Wójcik, "Propagation properties of photonic crystal fibers filled with nematic liquid crystals", Opto-Electron. Rev. 13, 177 (2005). DirectLink L. Scolari, S. Gauza, H. Xianyu, L. Zhai, L. Eskildsen, T.T. Alkeskjold, S.-T. Wu, A. Bjarklev, "Frequency tunability of solid-core photonic crystal fibers filled with nanoparticle-doped liquid crystals", Opt. Express 17, 3754 (2009). CrossRef Y.-S. Ha, H.-J. Kim, H.-G. Park, D.-S. Seo, "Enhancement of electro-optic properties in liquid crystal devices via titanium nanoparticle doping", Opt. Express 20, 6448 (2012). CrossRef T.R. Woliński, K. Szaniawska, S. Ertman, P. Lesiak, A.W. Domański, R. Dąbrowski, E. Nowinowski-Kruszelnicki, J. Wójcik, "Influence of temperature and electrical fields on propagation properties of photonic liquid-crystal fibres", Measur. Science Techn. 17, 985 (2006). CrossRef